Family-Centered Approaches to Pediatric Tuberculosis and Nutritional Challenges in North Aceh: A Qualitative Study - Mardiati; Anna Millizia; Noviana Zara; Khania Atika; Najwa Zakiyya (National Journal of Community Medicine)
Background: Pediatric tuberculosis (TB) remains a major global health issue, particularly in low- and middle-income countries. In areas such as Aceh, the nutritional needs of pediatric TB patients are frequently neglected, with treatment primarily addressing the causes of infection and insufficient family involvement. This study aimed to analyze the nutritional problems related to pediatric TB in North Aceh Regency, Aceh Province, Indonesia.